INDONESIA IN TOBACCO CONTROL EFFORTS TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS TARGET 3.A - Gatari Dwi Hapsari (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2019)
This paper entitled Indonesia’s effort in Tobacco Control to achieve 3.a targets of Sustainable Development Goals in 2017-2019, which is strengthen implementation of FCTC in all countries, as appropriate. This study is a fascinating case to research due to the growing prevalence of child smokers in Indonesia every year. The damage caused by this problem is multi-dimensional, which includes damage to the economy, economy, and social, even threatening the narration of the Indonesia Golden Era of 2045. This study supported by a sustainable development concept, non-military threat concepts, also public policy to divide the research title. Keywords: Indonesia, smoker prevalency, sustainable development goals, tobacco control.